2015
DOI: 10.1037/pas0000025
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the K6 Scale in a large school sample.

Abstract: Timely prevalence data of psychiatric morbidity among adolescents in small areas remains vital for mental health policy planning at the regional and local levels. Furthermore, effective regional policy planning also requires the measurement of psychiatric morbidity using clinically validated instruments. The K6 scale was therefore included on the 2012 administration of the Kentucky Incentives for Prevention Survey as a measure of serious emotional disturbance in the past 30 days. Principal axis and confirmator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 40 publications
12
47
0
Order By: Relevance
“…was some evidence of a possible second factor demonstrated by high eigenvalues, similar to what has been reported in U.S. and Australian adolescents (Mewton et al, 2016, Peiper et al, 2015. In contrast to a single factor solution, some earlier research has identified a two-factor structure in K6 (depression and anxiety) (Easton et al, 2017;Bessaha, 2017;Lee et al, 2012).…”
Section: Internal Consistency and Factor Structuresupporting
confidence: 72%
“…was some evidence of a possible second factor demonstrated by high eigenvalues, similar to what has been reported in U.S. and Australian adolescents (Mewton et al, 2016, Peiper et al, 2015. In contrast to a single factor solution, some earlier research has identified a two-factor structure in K6 (depression and anxiety) (Easton et al, 2017;Bessaha, 2017;Lee et al, 2012).…”
Section: Internal Consistency and Factor Structuresupporting
confidence: 72%
“…The internal reliability of the K10 for the present data set was excellent (Cronbach's  = 0.90). While a small number of studies advocate for K10 subscales for depression and anxiety (e.g., Brooks, Beard, & Steel, 2006), more recent population research indicates no empirical basis for a 2-factor structure (Peiper, Clayton, Wilson, & Illback, 2014;Sunderland, Mahoney, & Andrews, 2012). For descriptive purposes, cutoff scores for psychological distress were defined as low risk (sum score of 10-15), medium risk (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and high risk (30-50) (Furukawa, Kessler, Slade, & Andrews, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Our results, however, are consistent with findings from the National Comorbidity Survey Replication Adolescent Supplement (NCS-A) and other large population-based studies of adolescents. 11,12,14,19 Second, the sample size was modest, potentially leading to a Type II error. In particular, the extremely wide CI for lack of adult support suggests that future studies should utilize a larger analytic sample to derive more precise estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The significant findings for age, gender and living situation are broadly consistent with documented demographic differences in mental health. 10,19,20 Third, despite the distinct differences in presenting issues seen between classes, these groups do not represent diagnostic categories, nor does Jigsaw utilize clinical diagnoses to determine appropriate intervention planning. Whereas these factors may limit the ability to make clinical inferences with respect to specific disorders, the significant overlap between disorders suggests their classification as distinct disorders may not be theoretically or empirically meaningful.…”
Section: Discussionmentioning
confidence: 99%